How Ibrahim came to know Allah? - Khan, Saniyasnain; Gurmeet (Goodword Books New Delhi, 2008)
"How Ibrahim Came to Know Allah: Quran Stories for Little Hearts" is an engaging children's book that narrates the journey of Prophet Ibrahim (Abraham) as he seeks to understand the nature of God. Through simple, relatable language and vibrant illustrations, the story highlights Ibrahim's inquisitive spirit as he observes the world around him, questioning the existence of idols and the meaning of true divinity. His quest leads him to recognize Allah as the one true God. This inspiring tale encourages young readers to explore their own beliefs while emphasizing themes of faith, curiosity, and the importance of seeking knowledge about spirituality.